Comparison of serum oxidative status in healthy Arabian and Dareshoor horses - maryam karimi dehkordi (Islamic Azad University, Tabriz Branch, 2021)
Oxidative stress, which is an imbalance between the production of oxygen free radicals and the body's antioxidant defense, is strongly associated with physical activity during a horse's sporting life. The aim of the present study was to evaluate the serum levels of Malondialdehyde (MDA), total antioxidant capacity (TAC) and the antioxidant enzymes, superoxide dismutase (SOD), glutathione peroxatase (GPX) and catalase (CAT) as indicators of oxidative stress and to compare them between two horse races of Arab and Dareshoor. For this purpose, 26 non-pregnant and non-lactating female horses from Yazd province (13 Arab and 13 Dareshoor) were randomly selected. Blood samples were taken from all horses at rest. MDA, TAC and antioxidant enzymes were tested in the serum of the studied horses. The results showed that the rate of MDA in the serum of Arabian horses was significantly lower than Dareshoor horses (0.98±0.55 vs 1.59±0.56 µmol/L, respectively). Also, serum TAC concentrations in Arabian and Dareshoor horses did not show any statistically significant difference, although the rate of this parameter in Arabian horses was slightly higher than in Dareshoor (113.54±70.75 vs 112.56±53.93 µmol/L, respectively). In Arab race, level of SOD, GPX and CAT were also higher than Dareshoor. These differences between SOD and GPX enzymes were statistically significant (p<0.05). High levels of antioxidant enzymes and low levels of MDA indicate better health status for Arabian horses, and breed and genetics appear to play a role in enhancing the strength of the antioxidant defense system.